2013
DOI: 10.1002/lary.24052
|View full text |Cite
|
Sign up to set email alerts
|

Paracrine potential of fibroblasts exposed to cigarette smoke extract with vascular growth factor induction

Abstract: Objectives/Hypothesis Nicotine, a major constituent of cigarette smoke, can activate the cholinergic anti-inflammatory pathway by binding to α7-nicotinic acetylcholine receptor (α7nAChR) expressed on the surface of certain cells. Here, we ask whether cigarette smoke extract induced different paracrine factors compared to the in vivo regulator of inflammation, tumor necrosis factor-α, in human vocal fold fibroblasts (hVFFs) shown to express low levels of α7nAChR. Study Design In vitro. Methods α7nAChR was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 84 publications
(123 reference statements)
0
14
0
1
Order By: Relevance
“…Increased concentrations of TNF-α administered to cultured human vocal fold fibroblasts have been found to inhibit the rate of cell proliferation after 9 days (18). In contrast, Berchtold et al (17) observed no evidence of cell death after 24 hours following TNF-α administration to cultured human vocal fold fibroblasts. It remains unknown whether TNF-α initiates apoptosis or whether apoptosis leads to alterations in TNF-α.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Increased concentrations of TNF-α administered to cultured human vocal fold fibroblasts have been found to inhibit the rate of cell proliferation after 9 days (18). In contrast, Berchtold et al (17) observed no evidence of cell death after 24 hours following TNF-α administration to cultured human vocal fold fibroblasts. It remains unknown whether TNF-α initiates apoptosis or whether apoptosis leads to alterations in TNF-α.…”
Section: Discussionmentioning
confidence: 91%
“…In addition, there is evidence of tumor necrosis factor-alpha (TNF-α) upregulation in response to biomechanical trauma in the vocal folds (15, 16). However, studies reveal inconsistencies regarding the effect of TNF-α on cell death in the vocal folds (17, 18). To examine the relationship between TNF-α and apoptosis, a secondary purpose of this study was to determine whether gene transcript and protein levels of TNF-α are upregulated with increasing durations of vibration exposure.…”
Section: Introductionmentioning
confidence: 99%
“…5 Nicotine components of smoking stimulate angiogenesis, causing increased vascular permeability and therefore, forming subepithelial edema. 6 Kajek credited for RE with identification of edema at subepithelial compartment of vocal fold, which is superficial to vocal ligament, anteriorly bounded by Broyle's ligament and posteriorly by vocal process of the arytenoids. 7 Hirano has identified the subepithelial compartment of vocal fold as superficial lamina propria.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it has also been observed that cigarette smoke condensate increases intracellular reactive oxygen species, as well as heme oxigenase 1 and SOD1 gene expression in VFFs . Furthermore, VFFs are capable of participating in paracrine regulation of pathological blood vessel formation in cigarette smoking‐related Reinke's edema (cigarette smoke extract increases vascular endothelial growth factor) …”
Section: Discussionmentioning
confidence: 99%